1968
DOI: 10.1111/j.1532-5415.1968.tb02092.x
|View full text |Cite
|
Sign up to set email alerts
|

Fibrositis

Abstract: Abstract. Fibrositis—muscular or nonarticular rheumatism—is a controversial diagnosis; nevertheless it represents a real entity, whether primary or secondary. The outstanding symptoms are pain and stiffness. Objective findings are “trigger areas” and indurations. The most common sites are the soft tissues of the neck, shoulder, elbow, carpal tunnel, palms (Dupuytren's contracture) and low back, but sometimes the syndrome is generalized. Therapy for each type is outlined. The immediate treatment usually include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

1970
1970
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…He properly noted that men have more localized symptoms (pain) and signs (tender points) given that recent data have shown that men have fewer pain symptom sites and tender points than women [59,60]. Traut [57] discredits Stockman's [32] histologic observations, stating that such findings "had little substantiation." His important contribution was to bring into focus the systemic features of FMS (eg, fatigue, poor sleep, headache, and colitis).…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…He properly noted that men have more localized symptoms (pain) and signs (tender points) given that recent data have shown that men have fewer pain symptom sites and tender points than women [59,60]. Traut [57] discredits Stockman's [32] histologic observations, stating that such findings "had little substantiation." His important contribution was to bring into focus the systemic features of FMS (eg, fatigue, poor sleep, headache, and colitis).…”
Section: Discussionmentioning
confidence: 85%
“…The next important paper was by Traut [57] of the University of Illinois whose description of fibrositis in 1968 is fairly similar to the one used today. Traut [57] described female gender almost exclusively, generalized aching and stiffness, aching all over, fatigue, headaches, colitis, poor sleep, being "worry worts," and tender points on physical examination.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations